Work-related musculoskeletal symptoms among Traffic police: A Review - Leela Paudel; Naresh Manandhar; Sunil Kumar Joshi (Occupational Health and Safety Society of Nepal, 2019)
Workplace environment plays an important role in the health of the working population. The risk of adverse effects on health becomes high with the increase in duration of exposure to occupational hazards. Traffic police personnel are vulnerable to such situations. They undergo various hazards ranging from road injuries, physical hazards, biological hazards, chemical hazards, ergonomic hazards and psychological stress while they are at work. They have to keep on standing on same place throughout the duty hours, which also increases the risk of musculoskeletal problem. There have been very few researches to explore the situation of work-related musculoskeletal symptoms in traffic police. Recently, work-related musculoskeletal symptoms were the main cause of sickness absenteeism, reduction in productivity, and chronic occupational disabilities in traffic police have received much attention. Thus, this review has been designed to help the health care professional and occupational health and safety professionals to know the most prone body areas for Musculoskeletal Disorders so as to plan for ergonomic modification and improve quality of life of Traffic Police Personnel. It will also help in uplifting musculoskeletal health for Traffic Police Personnel.